Potential of carbon storage and sequestration in the Heroes Park City Forest, Purworejo Regency, Central Java - VIVI ASTUTI; INGGITA UTAMI; SRI WAHYUNINGSIH (Universitas Syiah Kuala, 2022)
Heroes Park City Forest has a high vegetation density in Purworejo Regency, Central Java province, absorbing and storing carbon from the atmosphere. This study analyzes the value of carbon stock, sequestration, and tree composition in the Heroes Park City Forest. Data collection was carried out in February 2021, using three randomly distributed 20 x 100 m plots. Analysis of carbon stock data, important value index, and diversity index was carried out quantitatively descriptively. The results showed that the carbon stock value of trees was 116.84 tons ha-1, which according to Reducing Emissions from Deforestation and Forest Degradation or REDD+, was included in the high carbon stock category. The value of carbon sequestration in Heroes Park urban forest is 428.80 tons ha-1, which is higher than some city forests in Indonesia. The sampling location is covered with 157 tree species, dominated by Acacia auriculiformis, and has a moderate level of tree diversity. Vegetation dominated by Acacia auriculiformis from Fabaceae contributed 43 percent of the total carbon stock in Heroes Park. Abiotics such as rainfall, air temperature, and humidity in Purworejo City support the growth of plants from the Fabaceae. Therefore, Heroes Park City Forest in Purworejo Regency has high carbon storage or carbon stock and sequestration values and needs to be monitored annually to maintain this potential.